2005
DOI: 10.1590/s0365-05962005000600006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de psoríase em estudo de 261 pacientes com vitiligo

Abstract: FUNDAMENTOS: O estudo da associação de psoríase e vitiligo é necessário em razão das prováveis origens imunológicas dessas enfermidades e da proximidade de loci encontrados no cromossomo 1p31. OBJETIVO: O propósito principal foi determinar a prevalência de psoríase em pacientes com vitiligo em amostra de 740 pacientes submetidos à fototerapia em Curitiba, PR e descrever suas características clínicas. MÉTODOS: Dos 740, foram estudados retrospectivamente 261 pacientes com diagnóstico de vitiligo, e analisados aq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…On the other hand, a Brazilian study found progression in 37.3% of cases. 25 We observed presence of family history in 10.6% of the cases, which amounts to the 9% reported in a Romanian population. 4 However, family history ranged from 34% to 38.7% in studies by other authors.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…On the other hand, a Brazilian study found progression in 37.3% of cases. 25 We observed presence of family history in 10.6% of the cases, which amounts to the 9% reported in a Romanian population. 4 However, family history ranged from 34% to 38.7% in studies by other authors.…”
Section: Discussionmentioning
confidence: 48%
“…However, age at onset showed a skewed distribution, with a median of 19 years (Q1 = 10.5 and Q3 = 40), ranging from 1 to 62 years. With regard to skin phototype, according to Fitzpatrick classification, the most common were skin phototype IV with 29.4% (25) and skin phototypes II and III, each with 28.2% (24); only 8.2% (7) had skin phototype V and 5.9% (5), skin phototype I. There were no patients with skin phototype VI.…”
Section: Resultsmentioning
confidence: 96%
“…The prevalence of psoriasis in patients with vitiligo has been reported to be 2.6% to 4.8%, which is not statistically significantly higher than in the general population. 20,21 The prevalence of psoriasis in our patients was slightly lower. Interestingly, many of our patients had a family history of psoriasis.…”
Section: Discussionmentioning
confidence: 48%
“…There were no differences in the prevalence of other autoimmune diseases between MS and NPSLE, although the one of autoimmune diseases among the patients' relatives was higher than in the general population. Headaches and References consciousness disorders also presented higher prevalence than those previously reported [21][22][23][24][25][26][27][28] .…”
Section: Discussionmentioning
confidence: 56%